Akhlak guru besar Sekolah Rendah Islam di Malang Indonesia / Triyo Supriyatno - Triyo, Supriyatno (2015)
This case study has focused on akhlaq of the principals’ in primary Islamic School, how they displayed understanding, feeling, and experience of akhlaq in surroundings of four principal’s Islamic primary school at Malang Indonesia. This case study utilized the qualitative approach design. Four principals, three from an urban and one from a rural area, were selected. Data were collected over nine months. The inquiry into akhlaq of the principals’ through the way caring was displayed in surroundings of four Islamic primary schools, as well as akhlaq acting was carried out by non-participant observation, unstructured interviews, documentation and principals’ journals. Data were analyzed using manual qualitative technique where codes were identified and themes were derived in order to answer the research questions. The findings of this study presented three major themes of understanding, appreciation and experience that has been conducted by the teacher in terms of probation as follows. Moral understanding of the relationship of the teacher understanding and practice, according to mahmudah morality based on al-Quran and as-Sunnah, mazmumah morality in conflict with al-Quran and as-Sunnah. Moral practice that has been emphasized is to appreciate the kindness of others, courtesy, charity, concern for the poor, cleanliness, discipline and honesty. The understanding of the procurement process in the practice of moral habituation; reasoning, research, and religiosity; and development of the mind. While the process of improving the Islamic ethic of goodness, cautious continuously of good practice, muraqabah, struggle, Tazkiyah al-nafs, with good friends, reading the Quran, and religious practices. It is not yet apparent relationship between faith and morality as founded by al-Ghazali. Appreciating moral teacher appreciation that had appeared on a muraqabah like prayer, studying the Quran and other such reflection realized the mistake and others. Experience a great moral teacher of moral experience providing teachers with struggle, demonstrations, uswah hasanah (best example). The overall findings of this study revealed that understandings, feeling and experience of akhlaq is not integrated, as how caring should be, as propagated by al-Ghazali. The study implied that the principals needed improvement in their understandings, feelings, and experiences in akhlaq acting in the midst of their followers. There should also be a change in the mode of the state and private examination based on Islamic ethics (akhlaq values) as principals need to be developed in a holistic manner, and the need for appropriate professional development on akhlaq values in the preparation, training and selection of principals. Lastly, an integrated and interactive approach that includes akhlaq values in developing principals’ competencies holistically is suggested to provide principals opportunities in experiential leading to develop relevant skills, besides acquiring knowledge, to better equip them to face their everyday and Islamic schools future lives.